Emergency Laparotomy in the Critically Ill: Futility at the Bedside - Niels D. Martin; Sagar P. Patel; Kristen Chreiman; Jose L. Pascual; Benjamin Braslow; Patrick M. Reilly; Lewis J. Kaplan (Critical Care Research and Practice)
Background. Critically ill patients are often evaluated for an intra-abdominal catastrophe. In the absence of a preoperative diagnosis, abdominal exploration may be offered despite desperate circumstances. We hypothesize that (1) abdominal exploration for such patients is associated with a high mortality and (2) commonly obtained physiologic measures at laparotomy anticipate mortality. Methods. All acute care surgery (ACS) patients undergoing emergency laparotomy at a quaternary referral center during a 3-year period were reviewed. Inclusion was defined by emergency laparotomy in the operating room (OR) in a patient with an American Society of Anesthesiologists (ASA) score ≥4 or bedside laparotomy in the ICU (BSL). Mortality was the primary endpoint and was stratified by demographics, admitting service, surgical findings, and physiology. Comparisons between OR and BSL were by Fisher’s exact and Mann–Whitney tests. Results. 144 patients underwent emergency laparotomy (45 BSL vs. 99 OR). Overall mortality was 55.6% (77.8% BSL vs. 45.5% OR; p<0.001). Mortality by admitting service was cardiac 71.4% (n=42), medical 70% (n=30), ACS 42% (n=50), and other 36.4% (n=22) services. Preoperative lactate levels were higher in nonsurvivors (2.7 vs. 8.5 mmol/L, p<0.001), as was vasopressor use (62.5% vs. 97.5%, p<0.001), acute kidney injury (51.6% vs. 72.5%, p<0.01), leukocytosis (53.1% vs. 71.3%, p<0.04), and anemia (45.3% vs. 71.3%, p<0.01). The presence of any identifiable abdominal pathology established a 90% mortality rate. Conclusions. The need for BSL portends an extremely high mortality rate and is likely useful in preintervention counselling. Emergency OR laparotomy leads to mortality in nearly half of such patients and is anticipatable based on concurrent abnormal physiology.